Seismic Moment Tensors of Padang 20090930 and Jambi 20091001 Events in Jambi using Three Component Local Waveforms: Identification of the Active Fault Plane - Madlazim Madlazim; Bagus Jaya Santosa; Widya Utama (Indonesian Journal of Physics, 2010)
A research has been conducted to estimate earthquake source parameters occurred on 30/09/2009 with 7.5 moment magnitude and 01/10/2009 with 6.4 moment magnitude. The event on 30/09/2009 was occurred in the sea and triggered by a mechanism related to subduction plane, while the one in 01/10/2009 occurred in the ground and triggered by the activity of Semangko Fault. The data used to determine the parameters of both earthquake source are three component local waveforms that are recorded by three MY broadband stations which belong to IRIS/Malaysia (IPM, KOM and KUM) and IRIS/Singapore MS network broadband station (BTDF). Availability of the three component local waveforms data is an opportunity to conduct a detailed research for earthquake source parameters in this area. In this paper, we report a focal mechanism of both events using Discrete Wave Number method to calculate the Green function and deconvolution iteration method to invert the tensor moment from three component local waveforms. Both methods are integrated in ISOLA_GUI software. The data is inverted at 35 mHz until 70 mHz to obtain the earthquake source parameters. Source parameters of both earthquakes (seismic moment, moment magnitude, orientation and fault plane and slip length) were extracted after double couple (DC) value were obtained and the reduction variant of each events are 99.3% and 70% and also 95.3% and 73%, respectively. To identify the fault plane, the HC-plot method is used, and to determine the length and width of the fault plane and also the slip length, an empirical equation is implemented in the Coulomb software. From the analysis, we obtain the type of fault for both earthquakes having strike, dip and rake angles that represent the fault plane orientation for both faults which are 88°, 70°, 146° and 149°, 49°, and -176°. The length and width of the fault and the slip length of both events are 124 km; 33.8 km; right lateral = 1.3 m and reverse slip = 0.88 m and also 22.68 km; 10.96 km; right lateral = 0.59 m and reverse slip = -0.04 m, respectively.